Effects of composition, thermal, and theological properties of rice raw material on rice noodle quality - Wei, Ping; Fang, Fang; Liu, Guoming; Zhang, Yayuan; Wei, Linyan; Zhou, Kui; You, Xiangrong; Li, Mingjuan; Wang, Ying; Sun, Jian; Deng, Sili (Frontiers in Nutrition, 2022)
The study aims to evaluate the relationships between characteristics of regional rice raw material and resulting quality of rice noodles. Four of most commonly used rice cultivars in Guangxi for noodles production were investigated. The results showed that compositions of rice flour primarily affected gelatinization and retrogradation, which then influenced the textural and sensory properties of rice noodles. Amylose content had strong positive correlation with peak viscosity (PV) and trough viscosity (TV) of rice flour (P < 0.01). PV and TV had strong negative correlations with adhesive strength (P < 0.01) and positive correlations with chewiness (P < 0.05), hardness, peak load and deformation at peak of rice noodles (P < 0.01). Protein content had positive correlation with the Setback of rice flour (P < 0.05), which is known to have influences on retrogradation. In addition, solubility had positive correlations with cooking loss (P < 0.01) and broken rate (P < 0.05) of rice noodles and strong negative correlation with its springiness (P < 0.01). Swelling power had negative correlation with broken rate (P < 0.05). As sensory score of rice noodles was negatively correlated with broken rate (P < 0.05) and cooking loss (P < 0.01) and positively correlated with springiness (P < 0.01), solubility and swelling power of rice flours were presumed to be useful for predicting consumer acceptability of rice noodles.